Improving medical induction in obstetrics and gynaecology. Issue 1 (19th September 2014) - Allen, Eve; Palmer, Edward; Lloyd, Jilly
Abstract: We present a year long quality improvement project to bring a new induction programme to the obstetrics and gynaecology (O&G) department of University Hospital Lewisham (UHL). Aimed at non-speciality junior doctors, including general practice and foundation trainees, the induction programme has sought to improve the quality of care delivered and experience of these transiting junior doctors. We have demonstrated a readily implementable and sustainable programme that requires only modest input of time from senior trainees (ST3+) periodically throughout the year. We have highlighted the specific need for senior consultant investment in the success and sustainability of such a project. We have demonstrated improvement of learning outcomes (p=0.01) in junior doctors undertaking the induction programme at Kirkpatrick's hierarchy level 2.